Anemia in patients receiving anticancer treatments: focus on novel therapeutic approaches - Bozzini, Claudia; Busti, Fabiana; Marchi, Giacomo; Vianello, Alice; Cerchione, Claudio; Martinelli, Giovanni; Girelli, Domenico (Frontiers in Oncology, 2024)
Anemia is common in cancer patients and impacts on quality of life and prognosis. It is typically multifactorial, often involving different pathophysiological mechanisms, making treatment a difficult task. In patients undergoing active anticancer treatments like chemotherapy, decreased red blood cell (RBC) production due to myelosuppression generally predominates, but absolute or functional iron deficiency frequently coexists. Current treatments for chemotherapy-related anemia include blood transfusions, erythropoiesis-stimulating agents, and iron supplementation. Each option has limitations, and there is an urgent need for novel approaches. After decades of relative immobilism, several promising anti-anemic drugs are now entering the clinical scenario. Emerging novel classes of anti-anemic drugs recently introduced or in development for other types of anemia include activin receptor ligand traps, hypoxia-inducible factor-prolyl hydroxylase inhibitors, and hepcidin antagonists. Here, we discuss their possible role in the treatment of anemia observed in patients receiving anticancer therapies.